2023
DOI: 10.31486/toj.22.0074
|View full text |Cite
|
Sign up to set email alerts
|

Adductor Canal Blocks Are Not Associated With Improved Early Postoperative Outcomes in Patients Undergoing Total Knee Arthroplasty

Abstract: Background: As length of stay after total knee arthroplasty (TKA) continues to shorten, interventions that may reduce early postoperative pain and complications must be studied. Peripheral nerve block is being explored as a potential means of improving pain management. The purpose of this study was to evaluate the impact of adductor canal block (ACB) on postoperative outcomes for patients undergoing TKA. Methods: We conducted a retrospective review of 565 patients who received unilateral TKA under spinal anest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, a case report suggested that the ACB may lead to impaired sciatic nerve function [ 19 ]. In other studies, the analgesic effect of the ACB were modest and clinically unimportant [ 2 , 20 , 21 ], Therefore, we believe that a single ACB may have limitations in the clinical setting.…”
Section: Discussionmentioning
confidence: 83%
“…However, a case report suggested that the ACB may lead to impaired sciatic nerve function [ 19 ]. In other studies, the analgesic effect of the ACB were modest and clinically unimportant [ 2 , 20 , 21 ], Therefore, we believe that a single ACB may have limitations in the clinical setting.…”
Section: Discussionmentioning
confidence: 83%